APPLICATION OF NON UNIFORM RATIONAL B-SPLINES AND SOFT BODY DYNAMICS IN THE THREE DIMENSIONAL MODELING AND ANIMATION OF GEOMETRIC SURFACES - admin, MODI, B; TIJJANIB.I (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
A central feature when sculpting, drafting, and painting objects based on the X, Y, and Z coordinate system is three dimensional (3D) modeling. The coordinate system distinctively specifies each point in a plane using a pair of numerical coordinates which forms the basic components of computer graphics and animation. This paper attempts to show the techniques used in modeling a water Seal named Flippy. The technique ranges from the use of primitive surface geometry object and soft body dynamics to the texturing of the animal while exploiting powerful shading groups. Flippy was later animated to play with a textured ball object for a few seconds. Additional features such as the rendering of entire scene and the modeling of the floor object using primitive polygons and lighting of the scene was applied. Lastly, ray tracing was added to give Flippy and the scene floor a reflective tile look.